Spatially Resolved Electron Transport through Anode‐Respiring Geobacter sulfurreducens Biofilms: Controls and Constraints. Issue 10 (3rd March 2021) - He, Xiaojia; Chadwick, Grayson; Jiménez Otero, Fernanda; Orphan, Victoria; Meile, Christof
Abstract: Microbial fuel cells (MFCs) with Geobacter sulfurreducens have been shown to produce high current densities; however, electron transport in G. sulfurreducens biofilms is not fully understood. Here, we utilize a spatially resolved numerical model describing this electron transfer to constrain mechanisms and controls on metabolic activity. Our model reproduces the metabolic activity profile obtained using nanoSIMS under positive (+0.24 V SHE) and negative (−0.1 V SHE) anode potentials. The simulations indicate that the distribution of the electric potential and pH both control cellular metabolism. Model simulations reproducing the experimentally determined activity patterns also support the presence of two activity modes in G. sulfurreducens biofilms, with a shift from a redox mid‐potential of −0.07 V SHE to −0.15 V SHE. Our model provides valuable insights into the fundamental mechanisms of electron transfer at Micron‐scale in conductive biofilms which can inform MFCs designs that maximize current production by minimizing the impact of inhibitory factors. Abstract : Direct extracellular electron transfer from Gebacter sulfurreducens biofilms to terminal electrodes is carried out via a chain of redox active molecules (e. g. cytochromes). The proposed model provides a theoretical framework describing this direct electron‐transfer process and is experimentally validated using stable isotope ( 15 N) probing with nanoSIMS.